Application of Drawing Therapy to Reduce Signs and Symptoms of Hallucinations in Nursing Care for Auditory Hallucination - Amalia Cintai, Rossa; Riyana, Asep; Cahyati, Peni; Somantri, Iwan (LPPM STIKes Muhammadiyah Ciamis, 2025)
Schizophrenia is one of the mental disorders that has reached 24 million cases out of 300 million cases of mental disorders in the world. The most common symptom that appears in schizophrenia is hallucinations, especially auditory hallucinations which are the most common cases of hallucinations where patients hear false voices. In minimizing the impact and reducing the signs and symptoms of hallucinations, there are several ways that can be used, namely pharmacological and non-pharmacological therapies. One of the nonpharmacological therapies that can be used is drawing therapy. The purpose of this case study is to determine the application of drawing therapy to reduce signs and symptoms in patients with auditory hallucination disorder. The theories underlying this scientific paper are schizophrenia, hallucinations, mental health care and scheduled activities which include the theory of drawing therapy. This study uses a qualitative design with a case study approach in two patients with auditory hallucination disorder. The results obtained showed a decrease in signs and symptoms after drawing therapy. The patient's ability also increased in controlling his hallucinations. The conclusion of this case study shows that drawing therapy is proven effective to control and reduce the signs and symptoms of hallucinations. It is expected that patients and families can cooperate in the treatment process, especially by increasing family support, client interest and motivation, and always controlling clients in drug compliance.